Anisotropic deformation and fracture mechanisms of physical vapor deposited TiN/ZrN multilayers. Issue 10 (July 2020) - Yang, Lingwei; Chen, Yunsheng; Chen, Jiao; Wang, Chuanyun; He, Guangyu
Abstract: This work focuses on the anisotropic deformation and fracture mechanisms of a typical physical vapor deposited TiN/ZrN multilayer, employing novel nanoindentation and micropillar compression techniques. The results highlight a stronger nanoindentation response of the multilayer when loaded perpendicular (90°) to the layer orientation, and the deformation was mainly controlled by the plasticity of ZrN layers. In comparison, at parallel (0°) orientation, the kink banding and the induced cracking may weaken the constraint beneath the indenter, thus leading to degraded hardness. By considering the anisotropic deformation mechanisms, nanoindentation finite element modeling was further performed to give reliable predictions on the strength at the inclined orientation. The modeling results suggest a dominant deformation mechanism that occurred mainly in the ZrN layers, with minor contribution from the stiff TiN layers. As a result, a minimized hardness was predicted at 45° loading direction with respect to layer orientation. Finally, the micropillar compressions show a brittle nature of both 90° and 0° oriented micropillars, and a higher fracture strain was obtained at 90°, due to the observed crack termination mechanism at this orientation.